A modelagem matemática na introdução ao estudo de equações diferenciais em um curso de engenharia - Ferreira, Vagner Donizeti Tavares (2010)
The research was aimed at the investigation on how the Modeling is used in the introduction of differential equations study in an engineering graduation course and how it can contribute to stimulate the skill to correlate Mathematics with everyday phenomena that involve variation besides the decision making about that phenomena, based on the information contained in the equation solution. The experiment took place at a private educational institution in São Paulo with fifteen voluntary students from different engineering courses who worked in groups of three people. Six activities were performed, developed according to the principles of Mathematical Modeling and Model Study, and held in four meetings. Three situations were explored during the activities: the first related to the automotive suspension system "Spring and Dashpot", in which the participants worked in either groups or open discussions encouraged by the researcher intervention, coming up to a mathematical model, solving the separated variable differential equation and opined about the meaning of the solution. The other two situations were adapted from Bassanezi (1988): in "Lakes Remediation" the problem was shown as well as the Mathematical Modeling and debated if the proposed solution in the book was like the one found in the previous situation; in the "Drugs Absorption" situation, only the problem was presented to verify if the participants could develop and solve the Model. The data analysis showed that students did the interpretation of the results, expressing the decisions made, for instance, in the "Lake Remediation" case indicating the increase of the water flow to accelerate the remediation process. In the "Drug Absorption" case they interpreted the problem and found the model and, by that, showed that the Mathematical Modeling helped the process to identify a mathematical equation as a useful tool in the important work of understanding and decision making about problems related to natural phenomena. As a follow up to this work it's suggested the study of the "Mass, Spring and Dashpot System" which will result in a second degree differential equation